Heat and mass transfer of a circular porous moist object located in a triangular shaped vented cavity - Selimefendigil, Fatih; Ozcan Coban, Seda; Öztop, Hakan Fehmi (Journal of Central South Univ, 2024)
Heat and mass transfer of a circular-shaped porous moist object inside a two-dimensional triangle cavity is investigated by using finite element method. The porous object is considered to be a moist food sample, located in the middle of the cavity with inlet and outlet ports with different configurations of inlet/outlet ports. Convective drying performance is numerically assessed for different values of Reynolds numbers (between 50 and 250), dry air inlet temperature (between 40 and 80 degrees C) and different locations of the port. It is observed that changing the port locations has significant impacts on the flow recirculaitons inside the triangular chamber while convective drying performance is highly affected. The moisture content reduces with longer time and for higher Reynolds number (Re) values. Case P4 where inlet and outlet ports are in the middle of the walls provides the most effective configuration in terms of convective drying performance while the worst case is seen for P1 case where inlet and outlet are closer to the corners of the chamber. There is a 192% difference between the moisture reduction of these two cases at Re=250, T=80 degrees C and t=120 min.
Keywords: convective drying; porous domain; cavity flow; inlet/exit port; finite element method